The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jcta.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The Manickam–Miklós–Singhi conjectures for sets and vector spaces

Abstract: More than twenty-five years ago, Manickam, Miklós, and Singhi conjectured that for positive integers n, k with n ≥ 4k, every set of n real numbers with nonnegative sum has at least n−1 k−1 k-element subsets whose sum is also nonnegative. We verify this conjecture when n ≥ 8k 2 , which simultaneously improves and simplifies a bound of Alon, Huang, and Sudakov and also a bound of Pokrovskiy when k < 10 45 .Moreover, our arguments resolve the vector space analogue of this conjecture. Let V be an n-dimensional vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…He reduced the conjecture to finding a k-uniform hypergraph on n vertices satisfying the MMS property (similar techniques were also employed earlier in [8]). The second conjecture, Conjecture 1.3, was very recently proved by Chowdhury, Sarkis, and Shahriari [3] simultaneously with our work. They also proved a quadratic bound n ≥ 8k 2 for sets.…”
supporting
confidence: 76%
“…He reduced the conjecture to finding a k-uniform hypergraph on n vertices satisfying the MMS property (similar techniques were also employed earlier in [8]). The second conjecture, Conjecture 1.3, was very recently proved by Chowdhury, Sarkis, and Shahriari [3] simultaneously with our work. They also proved a quadratic bound n ≥ 8k 2 for sets.…”
supporting
confidence: 76%
“…A 2012 breakthrough paper by Alon, Huang, and Sudakov [1] confirmed the conjecture for n ≥ 33k 2 . More recently, Chowdhury, Sarkis, and Shahriari [6] showed that the MMS conjecture is true for n ≥ 8k 2 . A linear bound was given by Pokrovskiy [21], who proved that the MMS conjecture holds, provided that n ≥ 10 47 k.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, if equality holds, the family of k-element subsets with nonnegative sum is a star on x 1 , S ∈ X k : x 1 ∈ S . The proof of Theorem 1.2 is similar to that of Theorem 1.3 in [9], where we tackle the Manickam-Miklós-Singhi conjectures for sets and vector spaces simultaneously. For the reader's convenience, we present the calculations for the case of sets in full detail in this unpublished manuscript.…”
mentioning
confidence: 88%
“…Although Conjecture 1.1 and the Erdős-Ko-Rado theorem share the same bound and extremal example, there is no obvious way to translate one question into the other. Conjecture 1.1 has attracted a lot of attention due to its connections with the Erdős-Ko-Rado theorem [1,2,3,4,5,6,7,8,9,11,13,14,16,17,18,19,20,21], but still remains open. For more than two decades, Conjecture 1.1 was known to hold only when k|n [18] or when n is at least an exponential function of k [4,6,17,21].…”
mentioning
confidence: 99%